ANALISIS FRAKSI-FRAKSI KURVA ISOTERMI SORPSI AIR DARI TEPUNG ROSELA DAN PENGARUHNYA TERHADAP SIFAT-SIFAT MUTU PRODUK [Analysis of Moisture Sorption Isotherm Fraction of Roselle Powder and Its Effect on Products the Quality Characteristics] - Rita Hayati (Jurnal Teknologi dan Industri Pangan, 2013)
The purpose of this study was to determine the fractions of moisture sorption isotherm curve and the critical water content of roselle powder and its effect on the product quality during storage. Roselle flowers were harvested at 25 days after flowering and sun dried (30ºC) for 3 days. The result showed that the moisture sorption isotherm curve of the roselle powder was sigmoid. The critical transition points among the three fractions of  the bound water in the roselle flour were first at moisture content (Mp) and water activity (ap) of 7.97% dry basis (db) and 0.23 respectively, and second at Ms 21.1% db water content and water activity (as) of 0.65%. Roselle powder samples were stored for 20 days at three relative humidity (RH) fractions represented by RH 22% (moisture content at 7.2% db), RH 57 % (20.5% db) and 84 % (54.2% db). The samples stored in the first fraction was stable in texture, colour and appearance, while the sample in the secondary bound water fraction (21.1% db), changed in colour into darker red. The sample stored in the tertiary bound water fraction (54.2% db) changed into brown colour with musty smell and mouldy after 15 days.